Quantum Networks with Deterministic Spin–Photon Interfaces. Issue 5 (10th April 2019) - Borregaard, Johannes; Sørensen, Anders Søndberg; Lodahl, Peter
Abstract: This report considers how recent experimental progress on deterministic solid‐state spin–photon interfaces enables the construction of a number of key elements of quantum networks. After reviewing some of the recent experimental achievements, a discussion of their integration into Bell state analyzers, quantum non‐demolition detection, and photonic cluster state generation is presented. Finally, it is outlined how these elements can be used for long‐distance entanglement generation and quantum key distribution in a quantum network. Abstract : This article discusses how the recent experimental progress on deterministic solid‐state spin–photon interfaces enables the construction of a number of key elements of quantum networks. The experimental achievements and their integration into Bell state analyzers, quantum non‐demolition detection, and photonic cluster state generation are discussed together with their applications within long‐distance quantum communication.